How is Europe positioned for a re-emergence of Schmallenberg virus? - Stavrou, Anastasios; Daly, Janet M.; Maddison, Ben C.; Gough, Kevin C.; Tarlinton, Rachael E. (Elsevier, 2017)
The Schmallenberg virus (SBV) caused a large scale epidemic in Europe from 2011–2013 infecting ruminants and causing fetal deformities after infection of pregnant animals. The main impacts of the virus were financial losses due to animal, meat and semen trade restrictions. Even though effective vaccines were produced, their uptake was never high. This along with the subsequent decline in new SBV infections and natural replacement of previously exposed livestock has resulted in a drop in the number of protected animals. Recent surveillance has found a large population of naïve animals currently present in Europe and the virus circulating at a low level. These changes in animal status in combination with favourable conditions for the insect vectors may open the door to the re-emergence of the virus and another large-scale outbreak in Europe. This review details the potential and preparedness for SBV re-emergence in Europe, discusses possible co-ordinated sentinel monitoring programmes both for ruminant seroconversion and the presence of virus in the insect vectors and provides an overview of the economic impact associated with diagnosis, control and the effect of non-vaccination.